Community filmaking in Ireland - Leahy, Eileen (Trinity College (Dublin, Ireland). Department of Film, 2014)
This thesis explores the state of the field of knowledge and looks at the limitations of current research. It identifies what the term community means and examines its importance for cinema. It defines community film and looks at the global context of community filmmaking in the different disciplines, sectors and contexts that use this term. An outline of the theoretical framework adopted explores the symbolic construction of community as defined by Anthony P. Cohen, the relationship between place and space as understood by David Harvey and by Doreen Massey as well as the cultural construction of the city as discussed by Michel De Certeau.
Keywords: Drama, Film & Music, Ph.D.; Ph.D. Trinity College Dublin